Implementation of Occupational Health and Safety (OHS) Standard Operating Procedures (SOPS) to Improve Work Safety on Tanker Ships: a Case Study on MT FTM 24 - Asur Supratman; K.P. Suharyono S. Hadiningrat; Febri Pramudya Wardani (Jurnal Cakrawala Akademika, 2025)
This study investigates the implementation of Occupational Health and Safety (OHS) Standard Operating Procedures (SOPs) aboard the MT FTM 24, a tanker vessel operating under international maritime regulations. The research aims to analyze the effectiveness of SOPs in improving work safety, identify challenges in their application, and provide recommendations for enhancing safety practices. Using a qualitative case study approach, data were collected through interviews, direct observations, and document analysis. The findings reveal that while SOPs are formally in place and compliant with standards such as the ISM Code and SOLAS, gaps remain in practical execution—particularly in training consistency, crew engagement, and behavioural safety integration. Crew understanding of SOPs varied based on rank, language proficiency, and operational experience. The study concludes that while SOPs contribute significantly to risk mitigation, their success depends on leadership support, continuous training, and a proactive safety culture. Recommendations include improving SOP accessibility, enhancing multilingual training, and establishing feedback mechanisms to support continuous procedural improvement. This research offers practical insights for shipping companies and contributes to the broader discourse on maritime occupational safety.